Biochemical Base for Estimation of the Production Potential of Microplankton Society in Waters of Bransfield Strait (Western Antarctica) at the Beginning of Autumn 2002 - Sysoev, A. A.; Sysoeva, I. V. (Ukrainian Antarctic Journal, 2005)
The production potential of pelagic society is determined, mainly, by autotrophic microplankton functional capacity for biomass replenishment owing to photosynthesis. The biomass increase, on the one part, is strong dependent on a ratio of autotrophic and heterotrophic components of microplankton society. Thus, it may be essential and quite enough to define the microbiota physiological state and autotrophic component quota for vector definition of microplankton society development. One of the most objective methods of microorganisms’ physiological state estimation is the adenilate energy charge (AEC) determination. AEC is calculated from adenine nucleotide (ATP, ADP and AMP) content ratio. It may theoretically lie in the range from 0 (with fully discharged system) up to 1 (with fully charged system). But substantively AEC varies in close limits during homeostasis: from 0.75 up to 0.99. The decrease of these values is evidence of organisms’ physiological depression degree. The heterotrophic-photoautotrophic (HP) index gives information about microplankton heterotrophic and autotrophic components ratio. PH index is calculated from ATP and chlorophyll "α" content ratio multiplied by 100 (for safe using). In case of HP is from 10 up to 20 it indicates the heterotrophic and autotrophic biomass parity. HP increase is evidence of heterotrophic predominance and HP decrease – about autotrophic predominance. Works were carried out in the 7-th Ukrainian Antarctic Expedition in March 2002 at 20 field stations between 62°50’ - 64°20’S latitude and 60° - 62°30’W longitude. The adenilates assays were carried out by sensitive chemiluminescent method. The chlorophyll “α” assays were carried out by the spectrophotometric method. The HP index analyses showed the autotrophic predominance in the vast area of the polygon, the considerable part of the region was reckoned in heterotrophic and autotrophic biomass equal area and insignificant part was with heterotrophic predominance. So one may conclude that AEC mainly reflected the physiological state of the autotrophic part of microplankton. Generally AEC changed from 0,39 up to 0,95 at average value 0,73. Despite of significant patchiness of AEC distributions, some prominent features of systems charge state are traced. The most oppressed physiological condition expressed in system discharging state up to threshold values of survival rates, was dated in the western and northern areas of the polygon, where the resource of biogenes is strongly exhausted owing to high biomass and acute pycnoclines, first of all, for phosphates. In spite of autotrophic predominance, the production potential is strongly reduced by the low level of AEC there. It should be expected the destruction processes predominance over production ones. On the contrary, on the greater part of polygon was under rather high degree of adenilate systems charged state. With considerable part of autotrophic content it testifies to high production potential uncharacteristic for late stages of succession is marked. Unfortunately, similar works in these latitudes were not carried out earlier and therefore there are no data to compare. But so high degree of adenilate systems charged state of microplankton society at the end of the vegetative season allows assuming, that the abnormal cold summer of 2002 with long-drawn freezing-over did not permit to gain a microplankton biomass on patterns of last years. This circumstance has to some extent saved a resource of biogenes for primary production during annual insolation peak and lag terms of microplankton development for the later period. This biochemical estimation method is especially convenient for high latitude waters due to the existence of the single-peak annual production succession.